2017
DOI: 10.1021/acs.jcim.6b00755
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Mechanical Study on the Catalytic Mechanism of Alkaline Phosphatases

Abstract: Alkaline phosphatases (APs) catalyze the hydrolysis and transphosphorylation of phosphate monoesters. The catalytic mechanism was examined by quantum-mechanical calculations using an active-site model based on the X-ray crystal structure of the human placental AP. Free energies of activation and of reaction for the catalytic steps were evaluated for a series of aryl and alkyl phosphate esters, and the computational results were compared with experimental values available in the literature. Mechanistic observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…The initial coordinates for the respective Michaelis complexes had been determined by previous molecular docking calculations. 10,12 In this complexes, the oxygen of the ester leaving group was coordinated to Zn 1 , and one nonbridging oxygen was coordinated to Zn 2 (Figure 1a). In the case of PLAP, the other two nonbridging oxygen atoms formed hydrogen bond interactions with the guanidinium group of Arg166 (the average O-H distances being 1.52 Å and 1.64 Å), and with a Mg 3 -bound water.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial coordinates for the respective Michaelis complexes had been determined by previous molecular docking calculations. 10,12 In this complexes, the oxygen of the ester leaving group was coordinated to Zn 1 , and one nonbridging oxygen was coordinated to Zn 2 (Figure 1a). In the case of PLAP, the other two nonbridging oxygen atoms formed hydrogen bond interactions with the guanidinium group of Arg166 (the average O-H distances being 1.52 Å and 1.64 Å), and with a Mg 3 -bound water.…”
Section: Resultsmentioning
confidence: 99%
“…This reaction step has been determined as rate-limiting for the enzymatic hydrolysis of alkyl phosphates. [10][11][12][13] Calculations were performed for hydrogen, methyl, and ethyl phosphate dianions as substrates. Computed energy changes are shown in Table 1, and the structures of stationary points are illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that hydrolysis of phosphomono-, phosphodi-, and phosphotriester substrates employ either the concerted D N A N or associative (A N + D N ) mechanism; a completely dissociative mechanism has not yet been observed for any of those substrate types. , The tightness of the transition state in these mechanisms, described in terms of the P–O­(nucleophile) and P–O­(leaving group) bond distances, decreases from mono- to triesters (Figure b) . Members of the binuclear metallohydrolase family have been proposed to employ a different mechanism depending on the nature of the substrate. ,,, …”
Section: Introductionmentioning
confidence: 99%